Report of the Study Group on the Welfare of the Weaker Sections of the Village Community Volume II - Ministry of Community Development (Ministry of Community Development, 1963)
The report on the welfare of weaker sections of the village community highlights the persistent socio-economic disparities in rural India and the need for targeted interventions to uplift marginalized groups such as landless laborers, scheduled castes, and tribes. It critiques prior development programs for favoring wealthier segments and emphasizes the importance of inclusive policies, decentralized decision-making through Panchayati Raj institutions, and robust economic and infrastructural support. Key recommendations include rural industrialization, cooperative farming, employment generation schemes, financial accessibility, educational initiatives, and coordinated community development programs. Additionally, the report underscores the integration of agricultural and industrial strategies, price stabilization, and participatory governance as essential components for sustainable rural development and equitable growth.
Ministry of Community Development, Panchayati Raj and Cooperation, Government of India New Delhi
Keywords: Weaker Sections; Rural Development; Panchayati Raj; Employment Generation; Agricultural Productivity; Rural Industrialization; Economic Planning; Cooperative Farming; Social Welfare; Education Initiatives; Infrastructure Development; Poverty Alleviation